A comparative study on the dielectric response and microwave absorption performance of FeNi-capped carbon nanotubes and FeNi-cored carbon nanoparticles. (10th December 2020) - Kuang, Daitao; Wang, Shiliang; Hou, Lizhen; Luo, Heng; Deng, Lianwen; Chen, Chuansheng; Song, Min; Mead, James L; Huang, Han
Abstract: The mechanisms responsible for the dielectric response of C-based microwave absorbers remain a long-standing theoretical question. Uncovering these mechanisms is critical to enhance their microwave absorption performance. To determine how different C forms alter the dielectric response of C-based absorbers, FeNi-capped carbon nanotubes (FeNi-CNTs) and FeNi–cored carbon nanoparticles (FeNi-CNPs) are synthesized, and a comparative study of their dielectric responses is then carried out in this study. The as-synthesized FeNi-CNTs and FeNi-CNPs have similar magnetic properties and complex permeabilities, but differ in complex permittivities. It is shown that FeNi-CNTs have a much stronger dielectric loss than FeNi-CNPs. At a thickness of 2.8 mm, a low optimal reflection loss of −32.2 dB and a broad effective absorption bandwidth of 8.0 GHz are achieved for FeNi-CNTs. Meanwhile, equivalent circuit models reveal that the CNT network of the FeNi-CNTs could introduce an electrical inductance that can effectively improve its dielectric loss capability. This study demonstrates that designing a composite with a tailored C form and composition is a successful strategy for tuning its microwave absorption performance. Furthermore, the equivalent circuit modeling is an effective tool for analyzing the dielectric response of the microwave absorbers, as is expected to be applicable for other metal-C composites.